Towards the synthesis of poly(azafulleroid)s: main chain fullerene oligomers for organic photovoltaic devices - Bregadiolli, Bruna A. [UNESP]; Ramanitra, Hasina H.; Ferreira, Rodrigo Marques [UNESP]; Corcoles, Laura; Gomes, Milton S.; Kang, Lauren; Combe, Craig M.S.; Silva, Hugo Santos; Lavarda, Francisco C. [UNESP]; Bégué, Didier; Dagron-Lartigau, Christine; Rocco, Maria Luiza M.; et al. (Wiley, 2017)
For the first time, imino chemistry is explored for the synthesis of main chain fullerene oligomers and low-molecular-weight polymers. Oligo(aziridinofullerene)s and low-molecular-weight poly(aziridinofullerene)s (PAFs) are prepared by 1,3-dipolar cycloadditions of bis(azidoalkyl) comonomers to C60. The effect of the steric bulk of the comonomer is studied and it is found that PAF solubilities and molecular weights are increased with longer comonomer side-chains. Initial and promising photovoltaic characterizations show commensurate improvements in properties. Interestingly, the PAFs exhibit lowest unoccupied molecular orbitals close to those of phenyl-C61-butyric acid methyl ester. Routine characterizations are correlated with DFT/B3LYP/6-31G(d) to understand structural and electronic behaviours. It is expected that higher molecular weights may be obtained through comonomer variations and that this novel methodology will open a route to interesting materials for optoelectronics. © 2017 Society of Chemical Industry.
Keywords: fullerene; oligo(aziridinofullerene); organic photovoltaic device; poly(aziridinofullerene); poly(fullerene)